RETRACTED: Pengembangan Sistem Informasi Pengukur Kesiapan Akreditasi Program Studi 9 Kriteria - Heliawaty Hamrul; Nuralamsyah Zulkarnaim; Aswad Tasdir (Journal of Applied Computer Science and Technology, 2021)
The accreditation system is a form of assessment (evaluation) of the quality and feasibility of higher education institutions or study programs carried out by independent organizations or bodies outside universities. The assessment is used as a quality benchmark for all study programs and higher education institutions, both from public and private universities that organize professional and academic programs. The better the value of accreditation will have an impact on the views of outsiders regarding the quality of the study program and higher education institution. However, the collection of data and information as well as filling out forms in the informatics study program still have many obstacles, such as the large number of data used as assessment criteria that requires a lot of time and effort. And also continuously accreditation that keeps repeating every few years is one of the problems faced in storing the accreditation data. ------------------------ Naskah ini telah di RETRACTED, silahkan baca https://journal.isas.or.id/index.php/JACOST/retraction. Naskah ini terindikasi publikasi ganda (Double Publication) yang telah terbit di https://ojs.unsulbar.ac.id/index.php/jcis/article/view/1251/745 (JCIS (Journal of Computer and Information System) Vol.4, No.2, Oktober 2021, Page 30 - 41 ISSN (print): 2622-5859, ISSN (online): 2622-0881 DOI:10.31605/jcis.v4i2)